Phylogeography and population structure of the global, wide host-range hybrid pathogen Phytophthora × cambivora - Mullett, Martin S; Van Poucke, Kris; Haegeman, Annelies; Focquet, Fran; Cauldron, Nicholas C; Knaus, Brian J; Horta Jung, Marilia; Kageyama, Koji; Hieno, Ayaka; Masuja, Hayato; Uematsu, Seiji; Webber, Joan F; et al. (IMA fungus, 2023)
Invasive, exotic plant pathogens pose a major threat to native and agricultural ecosystems. Phytophthora × cambivora is an invasive, destructive pathogen of forest and fruit trees causing severe damage worldwide to chestnuts (Castanea), apricots, peaches, plums, almonds and cherries (Prunus), apples (Malus), oaks (Quercus), and beech (Fagus). It was one of the first damaging invasive Phytophthora species to be introduced to Europe and North America, although its origin is unknown. We determined its population genetic history in Europe, North and South America, Australia and East Asia (mainly Japan) using genotyping-by-sequencing. Populations in Europe and Australia appear clonal, those in North America are highly clonal yet show some degree of sexual reproduction, and those in East Asia are partially sexual. Two clonal lineages, each of opposite mating type, and a hybrid lineage derived from these two lineages, dominated the populations in Europe and were predominantly found on fagaceous forest hosts (Castanea, Quercus, Fagus). Isolates from fruit trees (Prunus and Malus) belonged to a separate lineage found in Australia, North America, Europe and East Asia, indicating the disease on fruit trees could be caused by a distinct lineage of P. × cambivora, which may potentially be a separate sister species and has likely been moved with live plants. The highest genetic diversity was found in Japan, suggesting that East Asia is the centre of origin of the pathogen. Further surveys in unsampled, temperate regions of East Asia are needed to more precisely identify the location and range of the centre of diversity.
Keywords: Population genetics; Invasive pathogen; Polyploidy; Hybridization